Association of parent-child discrepancies in educational aspirations with physical fitness, quality of life and school adaptation among adolescents: a multiple mediation model - Hui Zeng; Bin Wang; Rui Zhang; Liangyu Zhao; Yuke Yang; Xiaosheng Dong; Yan Gao; Chenguang Gu (BMC, 2024)
Abstract Background The global public health issue of diminishing physical fitness among adolescents has gained increasing attention. The impact of parents' negative emotions or pressure regarding adolescents' educational aspirations may have a passive impact on the quality of life and adaptation of adolescents in and out of school, and ultimately harm their physical health. This study aims to explore whether parent-child discrepancies in educational aspirations influence physical fitness in adolescents through school adaptation and quality of life. Methods Participants consisted of 9,768 students, males 4,753(48.7%), females 5,015(51.3%), aged 11-19 years, males 14.3 ± 1.92, females 14.4 ± 1.93. The educational aspirations were gauged using a six-point scale for expectation scores. Physical fitness assessments were based on criteria from the National Student Physical Fitness and Health Survey. School adaptation was evaluated using the School Social Behaviors Scale-2. Quality of life for adolescents was measured using Chinese version of the Quality of Life Scale for Children and Adolescents. To analyze the multiple mediating effects, structural equation models were used, and 95% confidence intervals were determined through bootstrap methods. Results The results illustrated that school adaptation and quality of life played a significant mediating role in the effect of parent-child discrepancies in educational aspirations and physical fitness. There were three intermediary paths were confirmed: (1) discrepancies in educational aspirations → school adaptation → physical fitness (β=-0.088 SE = 0.021; p<0.01; 95% CI: -0.135, -0.05); (2) discrepancies in educational aspirations → quality of life → physical fitness (β=-0.025; SE = 0.011; p = 0.010; 95% CI: -0.050, -0.006); (3) discrepancies in educational aspirations → school adaptation→ quality of life → physical fitness (β=-0.032; SE = 0.014; p = 0.011; 95% CI: -0.061, -0.007). Conclusion This study suggests that parents should reduce negative emotions and pressure regarding adolescents' academic aspirations may help their children get better physical fitness.